2013
DOI: 10.1111/1365-2745.12098
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting changes in taxonomic, phylogenetic and functional diversity during a long‐term succession: insights into assembly processes

Abstract: Summary1. Theory predicts that the processes generating biodiversity after disturbance will change during succession. Comparisons of phylogenetic and functional (alpha and beta) diversity with taxonomic diversity can provide insights into the extent to which community assembly is driven by deterministic or stochastic processes, but comparative approaches have yet to be applied to successional systems. 2. We characterized taxonomic, phylogenetic and functional plant (alpha and beta) diversity within and between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
320
11
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 308 publications
(381 citation statements)
references
References 90 publications
35
320
11
2
Order By: Relevance
“…Estimates of the evolutionary divergence among different lineages within a community may be good surrogates for niche differences, assuming that changes in PD are proportional to changes in niche space or ecological function, i.e. that functionally relevant plant traits are phylogenetically conserved ( [20,21]; but see [25]). Consequently, the PD of a plant community is expected to be a comprehensive predictor for ecosystem processes, as demonstrated in experimental grasslands: more productive and stable plant communities had more evolutionary diverse lineages; PD was superior in predictive power compared with species richness or traits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Estimates of the evolutionary divergence among different lineages within a community may be good surrogates for niche differences, assuming that changes in PD are proportional to changes in niche space or ecological function, i.e. that functionally relevant plant traits are phylogenetically conserved ( [20,21]; but see [25]). Consequently, the PD of a plant community is expected to be a comprehensive predictor for ecosystem processes, as demonstrated in experimental grasslands: more productive and stable plant communities had more evolutionary diverse lineages; PD was superior in predictive power compared with species richness or traits [20].…”
Section: Introductionmentioning
confidence: 99%
“…For SLA, previous grassland studies have shown that imputation methods based on multiple imputation by chained equations may be used for filling gaps in functional trait databases [54]. Following Taugourdeau et al [54], estimates for missing values (approximately 9% of the species) were obtained using the multivariate imputation by chained equation (MICE) method [33,55,56]. Ellenberg indicator values were extracted from the JUICE database [57]: values for the four species that were not found in the database were extracted from Ellenberg et al [58].…”
Section: Plant Community Characteristicsmentioning
confidence: 99%
“…Previous studies have shown that grassland plant communities representing different stages in the arable-to-grassland succession are characterized by different habitat conditions and plant community characteristics [33,34]. Old grasslands have lower community-weighted mean values for Ellenberg indicators for nutrient and moisture availability than young grasslands [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of the simple idea that at the beginning of the succession the arrival of propagules is important, we expect a clustered or random structure of phylogenetic diversity and with the increasing importance of competition a trend towards overdispersion (e.g. Purschke et al, 2013).…”
Section: Introductionmentioning
confidence: 99%